ANALISIS CURAH HUJAN EKSTREM DI KEPULAUAN MALUKU DAN HUBUNGANNYA DENGAN FENOMENA ENSO - Khofaria, Hafizhu; Iskandar, Iskhaq; Suhadi (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2024)
Global climate anomalies can cause extreme climates, especially in Indonesia, one of which includes extreme rainfall events. Rainfall in Indonesia itself is coherent and correlated with ENSO variations in the Pacific Ocean. Apart from the influence of ENSO, there are other influences such as regional, local factors and regional topography which also greatly determine the characteristics of rainfall, especially in the Maluku Islands which have different rainfall patterns from other areas in Indonesia. The complex phenomena that influence rainfall in the Maluku region attract the attention of researchers to analyze extreme rainfall patterns and their relationship to ENSO relationships. This research uses daily rainfall data at BMKG and Metomanz stations from 1992 to 2022 for 30 years, and uses a simple linear regression method obtained from the results of ERA 5 reanalysis data with BMKG data, at stations that do not have complete data for 30 years. This research was conducted using the Mann-Kendall and Sen's Slope methods. The Mann-Kendall method is used to determine the degree of significance and change in positive or negative direction. Meanwhile, the Sen's Slope Method is used to determine the magnitude of the linear slope of the resulting trend. Extreme climate patterns in the Maluku Islands are influenced by the ENSO phenomenon and geographical conditions of the region. There are significant trend changes in CDD, CWD, and PRCPTOT. The Rnmm index is divided into three index limits (R20mm, R15mm, and R10mm). Increasing trends of CDD, CWD, PRCPTOT, occurred sequentially at Mathilda Batlayeri, Kuffar, Bandaneira stations. The Rnmm index is divided into three index limits R20mm, R15mm, and R10mm and there is a sequential increasing trend at Bandaneira, Namlea and Mathilda Batlayeri stations